2012
DOI: 10.1371/journal.pntd.0001447
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epitopes on Dengue Virus Envelope Protein Recognized by Monoclonal Antibodies and Polyclonal Human Sera by a High Throughput Assay

Abstract: BackgroundThe envelope (E) protein of dengue virus (DENV) is the major target of neutralizing antibodies and vaccine development. While previous studies on domain III or domain I/II alone have reported several epitopes of monoclonal antibodies (mAbs) against DENV E protein, the possibility of interdomain epitopes and the relationship between epitopes and neutralizing potency remain largely unexplored.Methodology/Principal FindingsWe developed a dot blot assay by using 67 alanine mutants of predicted surface-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(130 citation statements)
references
References 60 publications
13
117
0
Order By: Relevance
“…ZIKV-immune plasma was also found to cross-react with ZIKV and DENV1-4 E proteins ( fig. S11), possibly because of the abundant EDI/II cross-reactive antibody response (21,(26)(27)(28).…”
Section: Downloaded Frommentioning
confidence: 99%
“…ZIKV-immune plasma was also found to cross-react with ZIKV and DENV1-4 E proteins ( fig. S11), possibly because of the abundant EDI/II cross-reactive antibody response (21,(26)(27)(28).…”
Section: Downloaded Frommentioning
confidence: 99%
“…We then probed the folding state of the different proteins using mAb 4G2, which recognizes a DII conformational epitope on the fusion loop of all serotypes (Henchal et al, 1985;Lin et al, 2012). 4G2 recognized secreted DI/ DII and sE proteins from DENV3 and DENV4, as well as the secreted chimeras 2DI/3DII and 2sE(3DII) (Fig.…”
Section: Secretion Of E Ectodomain Depends On DIImentioning
confidence: 99%
“…Asp215 is important for infectivity 42 , a proven 41 and predicted 47 epitope, and a membranotropic region of the E protein (peptide 29) 67 .…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of α -helices in E-proteins using techniques (PAGAL 44, 45 ) previously applied to the Ebola virus 46 , revealed that α 1 in ZIKV-E and DENV-E proteins is not conserved in the sequence space. Furthermore, α 1 is perturbed in the post-fusion protein in DENV2-E protein 12 , and includes a known epitope that is not part of the pre-fusion α 1 41, 42, 47 . PAGAL analysis also highlights a cationic β -sheet within a putative GAG-binding domain 48, 49 , which consists of a pair of arginine residues that have significant electrostatic polarity reversal 48, 49 .…”
Section: Introductionmentioning
confidence: 99%